2003
DOI: 10.1002/anie.200351426
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid‐Derived Sulfides as Ultimate Organic Sulfur Compounds in Extensively Desulfurized Fuels

Abstract: Extremely hydrodesulfurization‐resistant organosulfur compounds of biological origin are present in trace amounts in highly desulfurized fuels. A series of these compounds (see picture; left) was characterized by mass spectrometry and NMR spectroscopic structural elucidation of the corresponding sulfones (right), which were isolated after selective oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…The thiapolycyclanes were derivates of thiophane condensed mainly with 5-membered rings. A series of novel, terpenoidderived polycyclic sulfides were identified by Charrié-Duhaut et al (2003) in highly desulfurized diesel oils and identified as 1,1,4a,6-tetramethyl-9-alkyl-1,2,3,4,4a,9b-hexahydrodibenzothiophenes.…”
Section: Sulfur Compounds In Crude Oil and Petroleum Productsmentioning
confidence: 99%
“…The thiapolycyclanes were derivates of thiophane condensed mainly with 5-membered rings. A series of novel, terpenoidderived polycyclic sulfides were identified by Charrié-Duhaut et al (2003) in highly desulfurized diesel oils and identified as 1,1,4a,6-tetramethyl-9-alkyl-1,2,3,4,4a,9b-hexahydrodibenzothiophenes.…”
Section: Sulfur Compounds In Crude Oil and Petroleum Productsmentioning
confidence: 99%
“…Refractory sulfur compounds are mainly DBTs with shielding structures, such as 4-DBT and 4,6-DBT, which are usually the dominant sulfur compounds in hydrogenated diesel and recognized as the most resistant sulfur compounds for hydroprocessing . In recent years, some sulfides have been found in crude oil with a stronger steric hindrance effect and are more difficult to hydrodesulfurize than 4,6-DBT . These compounds have characteristic biomarker skeletons and are considered to be the products of isoprenoids via sulfurization in early diagenesis. , The content of these compounds may vary greatly in crude oil.…”
Section: Conversion and Transformation Of Sulfur Compounds In Petrole...mentioning
confidence: 99%
“…In recent years, some sulfides have been found in crude oil with a stronger steric hindrance effect and are more difficult to hydrodesulfurize than 4,6-DBT . These compounds have characteristic biomarker skeletons and are considered to be the products of isoprenoids via sulfurization in early diagenesis. , The content of these compounds may vary greatly in crude oil. Therefore, it will be difficult to achieve ultradeep desulfurization if the feedstock contains a large proportion of straight-run diesel oil, which is traditionally considered to be a high-quality blending material for diesel production.…”
Section: Conversion and Transformation Of Sulfur Compounds In Petrole...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds with hexahydrodibenzothiophene (C 12 H 14 S) structures were reported in analyzed samples after a hydro-desulfurization process. 36 Hexahydrodibenzothiophenes (C 12 H 14 S) also have a DBE value of 6. If hexahydrodibenzothiophenes (C 12 H 14 S) were abundant, we would expect to see the product ions of dihydrobenzothiophene (C 8 H 8 S) as the saturated cyclic ring could be lost via molecular collision (refer to Figure 4).…”
Section: Energy and Fuelsmentioning
confidence: 99%